Is Biblical Studies Stuck in Antiquarianism?: The Case of Behemoth and Leviathan - Sneed, Mark R. (Journal of the bible and its reception, 2023)
In this article, a trajectory is traced that demonstrates that the soft consensus that Behemoth and Leviathan are the hippo and croc, respectively, is part of a larger phenomenon whereby these originally monstrous beasts have become domesticated and demythologized or their mythological nature rationalized. The great beasts as natural Egyptian animals only goes back to a 17th century Huguenot who was an etymologist, orientalist, antiquarian, and minister. This process of/domestication/demythologization in a weak form actually can be discerned in the Hebrew Bible itself but reaches its zenith during the Enlightenment. In the article, a trajectory of protest against this process is mapped out. And, finally, monsters are shown to be important theodicean agents in the ancient world as well as representing important mechanisms of cultural identity.